Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.29271/jcpsp.2019.12.s106
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Polyautoimmunity: Celiac Hepatitis, Grave's Disease and Autoimmune Hemolytic Anemia

Abstract: A 19-year female, diagnosed case of CD for eight years and GD for five years, presented at the Emergency Department with history of persistent jaundice for two months. There was also history of chronic diarrhea, fatigue and shortness of breath on exertion. She was receiving carbimazole, 10 mg, BID, and was admittedly non-compliant to both a gluten-free diet (GFD) and the medications. She had completely stopped taking the medications for six weeks at the time of presentation. On examination, the patient was hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“… 23 However, the association of AIHA with autoimmune hepatitis is a distinct condition rarely reported in children. 24 Literature supports the fact that it needs aggressive therapy with immunosuppression with steroids and Azathioprine. 25 Literature shows that patient respond well to treatment with resolution of symptoms as seen in our case.…”
Section: Discussionmentioning
confidence: 95%
“… 23 However, the association of AIHA with autoimmune hepatitis is a distinct condition rarely reported in children. 24 Literature supports the fact that it needs aggressive therapy with immunosuppression with steroids and Azathioprine. 25 Literature shows that patient respond well to treatment with resolution of symptoms as seen in our case.…”
Section: Discussionmentioning
confidence: 95%
“…12 Similarly, immunogenic factors, such as HLA-DQB1*0301, LRP1/STAT6, AIRE, and physiopathological mechanisms shared by ADS could determine biologic and nonbiologic drugs usefulness in MAS management. 7,12 Butt et al 13 suggested treating each AD separately, taking into account the clinical condition and individual aspects of each patient. On account of OCP progression and the risk of visual loss in our patient, treatment was based in a stepladder combined therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Различают первичные АИГА и вторичные АИГА, возникшие на фоне инфекций, аутоиммунных и онкологических процессов [24]. Описаны АИГА при кишечных инфекциях, аутоиммунных заболеваниях ЖКТ (целиакия, первичный билиарный холангит) [25,26,27], онкологической патологии пищеварительной системы (карциноиды, аденокарциномы) [28,29]. Развитие АИГА чаще опосредованно тепловыми антителами к эритроцитам, как правило, IgG 1 и IgG 3 типов, реже холодовыми антителами (IgM) [30].…”
Section: аутоиммунная гемолитическая анемия (аига) и патология желудо...unclassified